2018
DOI: 10.3906/sag-1707-207
|View full text |Cite
|
Sign up to set email alerts
|

Bedside measurement of the optic nerve sheath diameterwith ultrasound in cerebrovascular disorders

Abstract: Background/aim: We aimed to show the role of determination of optic nerve sheath diameter (ONSD) by bedside ultrasonography in an emergency department in the diagnosis of cerebrovascular disorders and its correlation with the clinical picture. Materials and methods:This prospective cross-sectional study included 55 patients with cerebrovascular disorders and 53 controls. Age, sex, ONSD, comorbid disease status, and multidetector computed tomography results of all subjects and application periods and National I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Its undue advantage among the other imaging techniques is due to its easy and wide availability, real time assessment, portable and non-invasive nature. 8 Ultrasound is often considered underutilized application with however a very wide potential in critical care including ocular pathology. 3 Studies have demonstrated utility of ultrasound in patients with traumatic brain injury as well as in non-traumatic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Its undue advantage among the other imaging techniques is due to its easy and wide availability, real time assessment, portable and non-invasive nature. 8 Ultrasound is often considered underutilized application with however a very wide potential in critical care including ocular pathology. 3 Studies have demonstrated utility of ultrasound in patients with traumatic brain injury as well as in non-traumatic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Komut et al 12 , a significant difference in the mean ONSD between patients with stroke (5.4 mm) and the control group (4.1 mm) was observed. Similarly, Yüzbasıoğlu et al 13 reported a significant difference in the mean ONSD between stroke patients (5.6 mm) and the control group (3.6 mm). In this study, the mean ONSD in the TIA group was determined to be 5.03±0.20 mm.…”
Section: Discussionmentioning
confidence: 81%
“…Such difference was found to be significant [4]. Yuzbasioglu et al [18] found the mean ONST diameter to be 5.6 mm for stroke patients; this value was 3.6 mm for the control group. This difference was found to be significant.…”
Section: Discussionmentioning
confidence: 89%